Answered prayers - Steel, Danielle (New York : Delacorte Press, 2002)
Trapped in unhappy marriages, childhood friends Faith Madison and Brad Patterson are reunited and rediscover companionship and laughter--perhaps now Faith can share a painful secret.
Keywords: Married women -- Fiction; Marital conflict -- Fiction; Friendship -- Fiction; Secrecy -- fiction; New York (N.Y.) -- Fiction; Psychological fiction